THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE BASIC SCHOOL SCIENCE AND BIOLOGY STUDY PROCESS - Porozovs, Juris; Āne, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The importance of Information and Communication Technologies (ICT) in educational process increases. The effective use of ICT in the study process could improve the knowledge of students and their interest about study process. The investigation was carried out in 5 Latvian schools. The questionnaire of 5-6 and 7-9 grade students about use of ICT during study process and attitude of students toward using of ICT in science and biology subjects was carried out. The results of the survey showed that the majority of students use ICT for study purposes until 1 hour or 1-2 hours during day but part of questionnaire students (14%) even more than 4 hours in a day. Students use ICT for different purposes: keep in touch with e-class, communicate with classmates, use computers and mobile phones for searching information in educational purposes, comply home works using computer and so on. The majority of questionnaire students consider that using of ICT help them in different areas of study process. Students to some extent agree that using of ICT give them ability to better understand science and biology subjects and increase motivation to learn these subjects.